Rare thymopharyngeal duct cyst presentation in an adult patient. Issue 2 (9th February 2021) - Wahi, Jessica Emilia; Delgado, Ruben; Medina, Ana Maria; Mesko, Thomas
Abstract : Retained thymic tissue may occur anywhere along the path of descent of the thymus. Cervical thymic cysts are a rare cause of benign neck masses. Thymopharyngeal duct cysts are thymic cysts that span the length of the neck and extend towards the mediastinum. These lesions are rare and classically have been described in paediatric patients. Here, we present the case of a 23-year-old woman with a left-sided neck mass, which was found to be a thymopharyngeal duct cyst. Multiple analytic modalities including the clinical presentation, imaging, operative findings and histology were required to confirm the diagnosis and are discussed below.